استخدام ليف شبكة براغ كمعوض للتشتت في أنظمة الاتصالات البصرية باستخدام برنامج المحاكاة Optisystem - عراج سهى (Latakia University Journal -Engineering Sciences Series, 2018)
إن الألياف البصرية هي واحدة من أهم وسائل الاتصال المستخدمة في أنظمة الاتصالات وقد تم استخدامها لنقل البيانات بسرعة عالية لمزاياها العديدة والضياعات المهملة في عملية النقل، ويعتبر التشتت العامل الرئيسي الذي يحد من كفاءة الأداء. هناك أنواع مختلفة من معوضات التشتت في الألياف البصرية ولكن يعتبر ليف شبكة براغ FBG هو الأكثر استخداماً في تعويض التشتت في أنظمة الاتصالات البصرية، بسبب الكلفة المنخفضة للمرشح المستخدم لاختيار طول الموجة وانخفاض فقد الحقن، حيث يملك طيف انعكاس منفصل وعرض حزمة واسع. سوف يتم تحليل محاكاة لنظام الاتصالات استنادًا إلى معايير مختلفة باستخدام simulator Optisystem ، واعتماد الإعدادات الأنسب للنظام والتي تشمل استطاعة الدخل وطول الكبل البصري)كم (ومعامل التخامد )ديسيبل/كم( الخاص بالليف البصري، وحسبت ثلاث معلمات مختلفة وتشمل كلا من استطاعة الإشارة، استطاعة الضجيج، الاستطاعة الخارجة عند المستقبل. Optical fiber is one of the most important communications media in communication system. Due to its versatile advantages and negligible transmission loss it is used in high speed data transmission. There are various types of optical fiber, the Fiber Bragg Grating (FBG) is commonly chosen as important components to compensate the dispersion in optical communication system. Because the low cost of filter for wavelength selection and low insertion loss, it has also customized reflection spectrum and wide bandwidth. The simulation of transmission system will be analyzed based on different parameters using OptiSystem simulator. By simulating a model of communication system and using the most suitable settings of the system which include input power, fiber cable length (km) and attenuation coefficient (dB/km) at cable section, there are three different parameters will be investigated, which are Signal power, Noise power, output power at receiver.